The use of THP-1 cells as a model for mimicking the function and regulation of monocytes and macrophages in the vasculature - Qin, Zhenyu (Atherosclerosis, 2012)
Since their establishment thirty years ago, THP-1 cells have become one of most widely used cell lines to investigate the function and regulation of monocytes and macrophages in the cardiovascular system. However, because this cell line was derived from the blood of a patient with acute monocytic leukemia, the extent to which THP-1 cells mimic monocytes and macrophages in the vasculature is not entirely known. This article serves as a meaningful attempt to address this question by reviewing the recent publications. The interactions between THP-1 cells and various vascular cells (such as endothelial cells, smooth muscle cells, adipocytes, and T cells) provide insight into the roles of the interconnection of monocytes–macrophages with other vascular cells during vascular inflammation, particularly atherogenesis and obesity. Transcriptome, microRNA profile, and histone modifications of THP-1 cells shed new light on the regulatory mechanism of the monocytes–macrophages in response to various inflammatory mediators, such as oxidized low density lipoprotein, lipopolysaccharide, and glucose. These studies hint that under certain defined conditions, THP-1 cells not only resemble primary monocytes–macrophages isolated from healthy donors or donors with disease, such as diabetes mellitus, but also mimic the in situ alteration of macrophages in the adipose tissue of obese subjects and in atherosclerotic lesions. A potential trajectory is to use this cell line to study the novel molecular mechanisms in monocytes and macrophages in relation to the physiology and pathophysiology of the cardiovascular system, however, the conclusion of studies employing THP-1 cells requires further verification using primary cells and/or in vivo models to be generalized to monocytes and macrophages.